INOVASI BMT: SOSIAL DAN KOMERSIAL BISNIS UNTUK PERTUMBUHAN EKONOMI - Hamdani, Hamdani (Investama : Jurnal Ekonomi dan Bisnis, 2023)
BMT as a sharia-based microfinance institution seeks to encourage economic improvement, economic equality and economic growth for the poor through social business programs. This is what Baitul Maal Wat Tamwil (BMT) Nurul Ummah Ngasem Bojonegoro is doing with two business models, through sharia microfinance products and sharia-based social programs. This research method uses a qualitative approach with a case study type approach. The focus of this dissertation is on the business model implemented by BMT Nurul Ummah Ngasem Bojonegoro with sharia savings products and sharia social programs for economic independence and community income. Meanwhile, testing the validity of the data and the validity of the data was carried out using the triangulation technique, namely a combined technique with various methods used to study the phenomenon of the research object. Data collection techniques were carried out by means of indepth interviews, observation and documentation on the objects studied. The products and programs were then analyzed using qualitative descriptive data analysis techniques. Referring to Miles and Huberman's theory, data analysis includes data reduction, data display, and data conclusion drawing verification